Experiences and lessons learned from mangrove conservation in China - Cheng, Gongshun; Liao, Huidan; Li, Xiaoxia (Frontiers in Forests and Global Change, 2025)
Mangrove forests are recognized as one of the most biologically diverse marine ecosystems on the planet, along with coral reefs and seagrass beds, and are known as the planet's three major marine ecosystems. As China has increased its efforts to protect mangroves on all fronts, the area of mangrove forests has grown steadily since the beginning of this century, and China is now one of the few countries in the world with a net increase in the area of mangrove forests. China's top-level design, legislation and practice, supervision, protection and restoration policies, publicity and education on mangrove protection have achieved noticeable results, and a mangrove protection model with Chinese characteristics has been explored and formed, and mangrove forests, the “guardians of the coast,” are becoming a shining business card of beautiful China. Therefore, China's important experience in striking a balance between mangrove protection and economic development can provide a reference for other mangrove areas worldwide, and is of great significance in solving the global problem of mangrove forests in danger.